Legume integration and nutrient management impacts on soil health and cropping system productivity - Feleke, Girma Wolde, author; Fonte, Steven J., advisor; Vivanco, Jorge, committee member; Manter, Daniel, committee member; Deiss, Leo, committee member (Colorado State University. Libraries, 2026)
Soil degradation threatens food security and livelihoods in sub-Sharan Africa and in smallholder farming systems globally. Thus, proper management of soil is critical for supporting long-term crop production and addressing multiple sustainability challenges in these agricultural systems. Integration of legumes into cropping systems, especially when combined with organic nutrient inputs, holds great promise for supporting soil health. However, legume performance and potential contributions to soil health, likely depend on legume species, management practices and inherent soil properties. The research considered here includes two field experiments in Ethiopia and a greenhouse study in Colorado to investigate the effect of: 1) integration of different legume species and residue retention on nitrogen fixation, soil health and carry-over benefits for subsequent crops, 2) distinct nutrient management strategies on soil health, crop performance and system profitability and 3) residue C input and soil N availability in regulating N fixation and associated microbial communities. To meet these objectives, I first established a field experiment in Ethiopia with three cropping phases. In phase 1, four legume species: 1) lablab (Lablab purpureus), a multipurpose legume, 2) cowpea (Vigna unguiculata), 3) common bean (Phaseolus vulgaris), and 4) soybean (Glycine max) were planted in a randomized complete block design. After legume harvest, each plot was divided into two residue management treatments (residue removal vs. retention), and chickpea (Cicer arietinum) was planted uniformly across all plots. Following chickpea harvesting, maize was planted in all plots. I used a 15N natural abundance approach to quantify the amount of atmospheric N fixed by the four legume species in phase 1. I found that lablab produced the highest biomass and fixed three times more atmospheric N than soybean or common bean. Legume residue retention improved multiple soil health parameters. Chickpea and maize grain yield were highest when lablab residues were retained, and were positively correlated with improved soil health metrics (organic matter pools, aggregate stability, available P). These findings suggest that integrating high-biomass legumes (with high N-fixation capacity) together with residue retention offers great promise for rapidly improving soil health in smallholder farming contexts, with extended benefits to productivity. For the next study, I established a separate field experiment in Ethiopia to examine the impact of three nutrient management strategies: 1) inorganic fertilizer, 2) manure, and 3) a control, with no nutrient inputs. These were combined with two legume species (common bean and soybean), in a full factorial design with four replicate blocks. Maize was planted in all plots in the following season to understand the residual impacts of the nutrient management and legume treatments on soil health and productivity. I found that manure applications substantially increased grain yield across both legumes relative to the control, while the fertilizer treatment yielded mostly intermediate values. Manure improved key soil health parameters as seen by reduced compaction (bulk density), as well as increased pH, soil organic matter fractions and available P. I also found that manure improved maize yield and net-profit relative to fertilizer and the control. My findings suggest that integrating legumes with manure application can improve soil health and crop yields, which in turn increase profitability for smallholder farmers growing legumes and maize in rotation. Finally, in a greenhouse experiment in Colorado, I used inputs of crop (wheat, Triticum aestivum) residues and nitrogen fertilizer to understand how soil carbon (C) and nitrogen (N) availability influence N fixation and associated rhizosphere microbial communities in cowpea. Cowpea was grown in pots containing soil amended with: 1) wheat residue alone, with a C:N ratio of 40 (high C:N), 2) wheat residue with urea to achieve a C:N ratio of 25 (medium C:N), 3) wheat residue with urea, for a C:N ratio of 15 (low C:N), 4) urea alone, and 5) no urea or residue inputs (control). Symbiotic N fixation was quantified using a 15N isotope dilution technique, while diazotroph abundance in the rhizosphere soil and cowpea nodules were assessed using nifH gene abundance. Full-length 16S rRNA sequencing was also used to profile rhizosphere bacterial communities. Cowpea growth was greatest in the urea and medium C:N treatments. Cowpea grown under the medium C:N fixed the highest amount of N, roughly doubled that observed in the other treatments. Additionally, the medium C:N treatment resulted in the greatest nodulation and the highest percentage of N derived from the atmosphere. In contrast, the low C:N and urea treatments appeared to inhibit nodulation and N fixation. Residue additions increased dissolved organic C and permanganate oxidizable C relative to urea and the control. Bacterial Shannon diversity and nifH gene abundance in the rhizosphere were highest in high C:N treatment, and the lowest under urea. Rhizosphere bacterial community structure differed among residue C and N inputs (PERMANOVA, p = 0.001), with both medium and high C:N inputs enriching in N-fixing bacteria, Rhizobium and Neorhizobium. These genera were positively correlated with labile C pools and negatively associated with NO3--N. My findings suggest that balancing residue C inputs with small N inputs (medium C:N) creates favorable rhizosphere conditions for symbiotic N fixation in cowpea nodules and the rhizosphere, providing a mechanistic basis for residue management strategies that support soil health and sustainable N management. The work presented here has important implications for smallholder farming systems. Overall, I found that selecting high-biomass, high N-fixing legumes, retaining residues, and prioritizing high quality organic nutrient inputs can improve soil health while enhancing crop productivity and profitability. These strategies offer a practical and scalable approach to soil health-centered intensification in resource limited environments.
Keywords: maize; rhizosphere; soil-plant-microbe interaction; N fixation; legumes; soil organic matter